Analisis Penerapan Fungsi Manajemen Dalam Pengelolaan Administrasi Usaha Mikro, Kecil, Dan Menengah - Putri, Rahmi Audina; Fadilah , Elviana; Safitri, Elsa Tiona; Iqrom, Aksya Robbi; Rifki , Ahmad (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study is to analyze the implementation of management functions in UMKM administration that are still not ideal. Many UMKM kesulitan menjaga efisiensi dan kelangsungan usaha due to the implementation of weak management functions, particularly in financial and operational administration. Perencanaan, pengorganisasian, pelaksanaan, and pengawasan are all included in management functions. UMKM has a crucial role in Indonesia's economy, yet many people are still unaware of how important money management is to increasing productivity. Effective financial management is essential for achieving optimal and sustainable pendapatan. The study findings indicate that MSMEs have successfully implemented financial management, although further assessment is still needed for each indicator. To advance, MSMEs are encouraged to implement more digital and systematic financial systems, such as cloud-based accounting technology. Furthermore, human resource capacity building through research and development from relevant institutions is also encouraged. With these initiatives, MSMEs are expected to become more stable, grow, and achieve strong sales, both domestically and internationally.